PENGARUH KECERDASAN EMOSIONAL TERHADAP PERILAKU AGRESIF MELALUI MUSIK KLASIK PADA MAHASISWA PSIKOLOGI ANGKATAN 2023 - Sefni Rama Putri; Mega Tangkudung; Friska Oktaviana Banyamin; Ayu Riana Tuna; Zafirah Manoppo; Anggita S. Kadue (Elsia: Jurnal Psikologi Manusia, 2024)
Adolescence is an important developmental period marked by biological, cognitive, and socio-emotional changes. These changes require adolescents to adapt effectively in various aspects, including physical, personality, intellectual, and roles in the family and environment. Imbalances in the adaptation process can cause identity confusion and make adolescence a crucial phase in the formation of self-identity. Emotional intelligence (EQ) plays an important role in helping adolescents face these challenges. EQ includes the ability to recognize, understand, cope with, and express emotions appropriately. In addition, emotional intelligence supports the development of cognitive potential and academic success. Adolescents with good EQ are better able to manage their emotions, so they can achieve balance in life and optimize their potential in school and social environmentsAdolescence is an important developmental period marked by biological, cognitive, and socio-emotional changes. These changes require adolescents to adapt effectively in various aspects, including physical, personality, intellectual, and roles in the family and environment. Imbalances in the adaptation process can cause identity confusion and make adolescence a crucial phase in the formation of self-identity. Emotional intelligence (EQ) plays an important role in helping adolescents face these challenges. EQ includes the ability to recognize, understand, cope with, and express emotions appropriately. In addition, emotional intelligence supports the development of cognitive potential and academic success. Adolescents with good EQ are better able to manage their emotions, so they can achieve balance in life and optimize their potential in school and social environments